Spectral Efficiency Improved 2D-PAM8 Trellis Coded Modulation for Short Reach Optical System - Yan Fu; Meihua Bi; Da Feng; Xin Miao; Hao He; Weisheng Hu (IEEE Photonics Journal)
This paper proposes and demonstrates a 31.25 Gbps two-dimensional eight level pulse amplitude modulation with trellis coded modulation (2D-PAM8-TCM) transmission in intensity modulation and direct detection based short reach system. In this system, the commercial directly modulated laser and photodiode with trans-impedance amplifier (PIN-TIA) with a combined modulation bandwidth of ∼16 GHz are used as transmitter and receiver, respectively. For 2D-PAM8-TCM signals, except for regular 8-state convolutional encoder, both 16-state and 32-state encoders are provided. Considering the coding gain and the complexity of convolutional encoder, the 16-state one is recommended. Moreover, instead of Viterbi decoder, the M-algorithm is utilized at the receiver side to reduce decoder complexity. It is experimentally demonstrated that 2D-PAM8-TCM scheme can achieve 2.5 b per symbol and ∼0.5 dB sensitivity improvement (bit error rate @ $3.8 × {10^{ - 3}}$ ) over a 20 km standard single mode fiber in comparison with conventional PAM4. Thanks to no additional digital signal processing in receiver side except M-algorithm, this scheme is simple and effective, which can be considered as an attractive technique for future short reach system.